Hubungan Kontrasepsi IUD (Intra Uterine Device) Pascasalin 40 Hari Dengan Produksi ASI Pada Ibu Nifas - Dukiyah, Dukiyah; Sunanto, Sunanto; Hanifah, Iis (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
The Family Planning Service (KB) program in Indonesia is experiencing a stagnant situation which is marked by the lack of increasing several indicators of family planning services, namely the number of participation in family planning (Contraceptive Prevalence Rate = CPR) and unmet need). This study aims to analyze the relationship between 40-day postpartum IUD (Intra Uterine Device) Contraception and Breastmilk Production in Postpartum Mothers in the Work Area of Sumber Health Center, Probolinggo Regency. This research is a quantitative research design with a correlational design using a cross sectional study approach with 33 respondents using accidental sampling technique. Data collection includes coding, editing and tabulating, then analyzed manually and computer with Chi Squaren Test. Based on 33 respondents, most of the IUD Contraceptives were Exactly as many as 20 respondents (60.6%) including those whose breast milk production was current, 15 respondents (45.5%) and those that were not smooth, as many as 5 respondents (15.2%) and obtained P Value: 0.003 and a= 0 ,05 means r < a, so H0 is rejected and Ha is accepted, and there is a relationship between 40 Day Postpartum IUD (Intra Uterine Device) Contraception with Breast Milk Production in Postpartum Mothers in the Work Area of Sumber Health Center, Probolinggo Regency. It is hoped that breastfeeding who does not want to get pregnant again, of course requires safe contraception, does not interfere with the breastfeeding process nor does it affect milk production. There are various personal reasons to regulate the number and spacing of children desired, reducing the risk of contracting sexually transmitted diseases.